When Winning is Losing: Arkansas River Interstate Water Management Issues - Harrington, Lisa M. Butler; Harrington, John A., Jr. (My University, 2005)
As the accessibility of local groundwater reserves declines, the quality of Arkansas River water flowing into southwestern Kansas is becoming a major concern. The Arkansas is a regulated river with significant diversions for irrigation occurring in eastern Colorado. Irrigation return flows have impaired the quality of water entering western Kansas. Salinity levels have the potential to impact both the alluvial aquifer and High Plains/Ogallala aquifer waters. In this paper. we document the significant changes in the nature of local water resource utilization based on archival research. We then present results from stakeholder interviews designed to obtain local knowledge regarding sensitivity and adaptive capacity to hydroclimatic variabiliity.
Keywords: Hydroclimatic variability; Ogallala aquifer; Irrigation; Groundwater